Weak solutions for a fluid-elastic structure interaction model - Desjardins, B.; Esteban, M.J.; Grandmont, C.; Le Tallec, P. (Revista Matemática Complutense, 2001)
The purpose of this paper is to study a model coupling an incompressible viscous fluid with an elastic structure in a bounded container. We prove the existence of weak solutions “`a la Leray” as long as no collisions occur